Notice of Patrick Chalmers, M.D., of Haselhead and Fedderat, Professor of Medicine in Aberdeen, and of his Practice as a Physician in the end of the seventeenth and beginning of the eighteenth century - Chalmers, John I (Proceedings of the Society of Antiquaries of Scotland, 1862)
The article begins with a short biography of the life and family of Dr Patrick Chalmers, a physician in Aberdeen. The author then focuses on the contents of Dr Chalmers’ ledger, which he used to record the activities of his medical practice including the prices for the treatment of various people and ailments. Meeting notes from 8 April, 1861 are appended.